South Asia migration report 2020
1 online resource
Keywords: South Asia Migration Report 2020 documents key themes of exploitation and entrepreneurship of migrants from the region. This volume: Includes dedicated fieldwork from India, Pakistan, Bangladesh and Nepal; Analyses the impact of South-Asia-migrant-established businesses; Examines legal and legislative recourse against exploitation in destination countries; Factors in how migration as a phenomenon negotiates with gender, environment and even healthcare. This book will be indispensable for scholars and researchers of economics, development studies, migration and diaspora studies, gender studies, labour studies and sociology. It will also be useful to policymakers, think tanks and government institutions working in the area.